Kepadatan Nyamuk Mansonia dan Anopheles dengan Prevalensi Penyakit Filariasis di Kecamatan Taniwel Kabupaten Seram Bagian Barat - Johanis Fritzgal Rehena; Sriyanti Imelda Aksamina Salmanu; Theopilus Wilhelmus Watuguly (Department of Biology Education, FSTT, Mandalika University of Education, Indonesia., 2021)
Filariasis is an infectious disease caused by filarial worms and transmitted by Mansonia and Anopheles mosquitoes. The prevalence of filariasis is influenced by the density of Mansonia and Anopheles mosquitoes. The purpose of this study was to determine the density of Mansonia, Anopheles mosquitoes, and zoonotic animals, and their relationship to the prevalence of filariasis in Taniwel District, West Seram Regency. This type of research is survey research and case control. The population in this study was the density of Mansonia and Anopheles mosquitoes, and cases of filariasis. While the research sample is people who suffer from filariasis, larval density, Mansonia and Anopheles mosquitoes. Data on the density of larvae/mosquitoes of Mansonia and Anopheles were analyzed descriptively, and analysis of the relationship between density of community habits and prevalence of filariasis was carried out by using the chi square test with SPSS version 20.0 program. The results showed that people used mosquito repellent lotion or brought mosquito rackets before doing activities at night. The density of Mansonia mosquitoes in Sohuwe Village is 4.00-5.85; Lumahlatal Village 5.00-6.60; and Maloang Village 4.00-6.20. Meanwhile, the density of Anopheles mosquitoes in Sohuwe Village is 7.00-9.85; Lumahlatal Village 5.89-6.82; and Maloang Village 5.00-6.50. The prevalence rate of filariasis in Sohuwe Village is 0.66; Lumahlatal Village 0.88; and Maloang Village 1.54; and there is a significant relationship between people's habits and the incidence of filariasis.